Problem-Based Learning versus Traditional Learning in Physics Education for Engineering Program Students - Liutauras Marcinauskas; Aleksandras Iljinas; Jurgita Čyvienė; Vytautas Stankus (MDPI AG, 2024)
Problem-based learning (PBL) is an educational method which involves learning by solving real problems. However, applying a PBL approach to engineering subjects in some cases became a challenging issue. Thus, it is important to determine the best ways in which engineering students can learn physics more effectively and solve problems relevant to their daily lives. The main aim of this study was to compare the final assessment grades in a physics course for students in the engineering program using PBL and traditional learning (TL) methods. The advantages and disadvantages of PBL and TL methods from the practical experience of lecturers are also presented. The study presented data of 460 first-year engineering students taking the physics course at Kaunas University of Technology. The information presented in this study is based on the insights, observations, and individual experiences of the authors as teaching staff. The results indicated that the application of the PBL method allows for enhancement in the teamwork, presentation, and critical thinking skills in physics. However, the TL method promotes the individual learning skills and wider theoretical knowledge in physics of students and is more suitable when the exam only includes closed-ended questions.